2019
DOI: 10.1080/10641963.2019.1590386
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of muscle power training on blood pressure in elderly patients with type 2 diabetes mellitus

Abstract: The aim of the present study was to evaluate the effects of 12 weeks of muscle power training (MPT) on casual blood pressure (BP) (before and after each training session) and resting BP (pre-and post-training program) in type 2 diabetes mellitus (T2DM) elderly. Methods: Twelve T2DM elderly individuals (68.75 ± 7.83 years), non-insulin-dependents participated in the present study and performed the MPT program twice a week. Casual BP was measured before and after training sessions, and resting BP was measured 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
(77 reference statements)
0
6
2
Order By: Relevance
“…Different from previous studies that have assessed BP post-exercise during a very short-term period in a laboratory setting [10,11,25], the present study showed in a sample of hypertensive older women that a HVRE session elicited a systolic PEH up to 4 h post-exercise in free-living conditions. This BP reduction observed in the present investigation may have attenuated the overload imposed to the subjects' cardiovascular system during their daily activities, which is clinically meaningful.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Different from previous studies that have assessed BP post-exercise during a very short-term period in a laboratory setting [10,11,25], the present study showed in a sample of hypertensive older women that a HVRE session elicited a systolic PEH up to 4 h post-exercise in free-living conditions. This BP reduction observed in the present investigation may have attenuated the overload imposed to the subjects' cardiovascular system during their daily activities, which is clinically meaningful.…”
Section: Discussioncontrasting
confidence: 91%
“…No changes were observed for BP, despite a lower HR and an increased NO bioavailability 30 min post-exercise. Although discrepancies exist among the investigations, the present results and others [11,25] suggest that a power exercise or HVRE session elicits PEH in hypertensive older adults.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…week with moderate intensity. 43 After 20 weeks of high-intensity RT with a frequency of 2 sessions per week, the central SBP and DBP were significantly reduced by 6 and 3 mmHg, respectively, in healthy men and women. Brachial BP also showed a significant reduction.…”
Section: Discussionmentioning
confidence: 88%
“…Significant changes in resting SBP and DBP were not observed in the elderly with diabetes mellitus 48 hours after the last session of 12 weeks of RT. Exercises were performed twice a week with moderate intensity 43 . After 20 weeks of high‐intensity RT with a frequency of 2 sessions per week, the central SBP and DBP were significantly reduced by 6 and 3 mmHg, respectively, in healthy men and women.…”
Section: Discussionmentioning
confidence: 99%